The Effect of Contextual Teaching And Learning (CTL) Learning Model Assisted by Android-Based Application Media Whith Thunkable On Learning Interest Of Class V SDN Students Candirejo 02 - Agus Arifin Rohmatullah Arif; Kartika Yuni Purwanti (Jurnal Sekolah Dasar, 2021)
This study aims to determine the effect of contextual teaching and learning (CTL) learning models assisted by android-based applications with thunkable on students' interest in learning. This type of research is an experiment with a pretest - posttest control group design. The population in this study were all students of SDN Candirejo 02, Ungaran Barat District, Semarang Regency, then for the research sample was class 5 SDN Candirejo 02, Ungaran Barat District, Semarang Regency with random sampling techniques. The data collection technique used is the scale of observation, tests, questionnaires (questionnaires) and documentation. Data were analyzed by normality test, homogeneity test, t test and regression test. The results of the research show: (1) There are differences in the use of contextual teaching and learning (CTL) learning models assisted by android-based applications with thunkable on students' learning interest, this is evidenced by the significance level > 0.05, i.e. 0.000 > 0.05 using the t test (2 ) There is an effect of the use of contextual teaching and learning (CTL) learning models assisted by android-based applications with thunkable on students' interest in learning, this is evidenced by a significance level of < 0.05, i.e. 0.000 > 0.05 using a regression test. The results of this study can be concluded that the contextual teaching and learning (CTL) learning model assisted by android-based applications with thunkable has an effect on increasing student interest in learning.